Does trade tariff liberalisation matter for Intra-ECOWAS trade? - Mohammed I. Shuaibu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The purpose of this paper is to examine the relationship between trade liberalisation and intra-regional trade in some selected ECOWAS member countries, with particular focus on the role of applied and most favoured nation import tariffs. Design/methodology/approach - Data utilized were sourced from the World Bank's World Development and Governance Indicators, Mayer and Zignago (2006) distance index as well as the World Trade Organisation's World Integrated Trade System (WiTs). The sample period consists of 8 countries covering the years 1998 to 2011. Predicated on a gravity framework, system and difference generalised method of moments dynamic panel data estimators were relied upon. Findings - The empirical results showed that trade liberalisation has contributed to intra-regional trade in the West African sub-region. The potency of trade liberalisation was relatively more pronounced through the use of most favoured nation import tariff compared to applied import tariff rates. Our results also showed that improved institutional quality and infrastructure are associated with higher intra-ECOWAS trade. Furthermore, using alternative measures of institutional quality and infrastructure as well as fixed and random effect estimators validated our findings. Research limitations/implications - Data limitations led to the inclusion of only 8 out of the 15 ECOWAS member countries in the sample. The research was also limited to tariff barriers as measure of trade liberalisation. The same methodology can be applied as data becomes available while a consideration of non-tariff barriers could provide more insights on the dynamics of intra-ECOWAS trade. Originality/value - The findings reinforce the notion that removal of trade restrictions particularly in the manufacturing sector, good governance and infrastructural developments enhance trade amongst ECOWAS countries.
Keywords: F13; F15; C3; 330; Intra-ECOWAS trade; trade liberalisation; import tariffs; difference GMM and system GMM